Fabrication of Natural Gelcoats (Epoxy/ Pumpkin Peels Fibers) Composites with High Mechanical and Thermal Properties - Qasem Fadhel, Afya; Hamdi Jassim , Widad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Pumpkin waste powder was used as a coloring and strengthening filler in epoxy to prepare a natural gelcoat . The Pumpkin powder was mixed with different weight ratios (1, 2, 3, 4, 5, 6, 7, and 8%) to the epoxy matrix to select the best value of powder addition. The effect of the pumpkin particle size on the mechanical properties (impact, flexural, hardness, and wear loss) using two different sizes (2.5 and 1.25 microns) was studied. The impact strength increased from (10.09 KJ/ m2) for neat epoxy to (14.79 KJ/ m2) for epoxy with  1% of micron pumpkin fibers ( MPF) with particle size 2.5 micrometer and (14.21 KJ/ m2) for epoxy with 4% (1.25 MPF), flexural strength increased from (41.94 MPa) for neat epoxy to (~ 46 MPa) for epoxy with  1% of  2.5 MPF  and to (50.17 MPa) for epoxy with 4% of 1.25 MPF, hardness of neat epoxy was (~ 77) and almost maintained its value for epoxy with  1% of 2.5 MPF and for epoxy with 4%  of 1.25 MPF. At almost the weight fractions addition of pumpkin fibers to epoxy, the (EP/1.25MPF) composite shows a higher wear resistance than the (EP/2.5MPF) composite. The density, thermal conductivity, and water diffusion (for 1-4 weeks' immersion) of (EP/2.5MPF) and (EP/1.25MPF) composites were carried out at different weight percentages of pumpkin fibers. SEM and EDS techniques were employed to fix the microstructure and the elemental composition of (EP/2.5MPF) and (EP/1.25MPF) composites, respectively. The internal structure of the composites has been linked with their macroscopic characteristics, such as the color degree of natural gelcoats and their mechanical and thermal properties.